Emergency response in overturned pig transport vehicles: Description and discussion of Danish cases from a One Welfare perspective - Cecilie Kobek-Kjeldager; Kirstin Dahl-Pedersen; Mette S Herskin (Animal Welfare)
Based on experiences from stakeholders, this paper describes and discusses Danish emergency procedures when animal transport vehicles overturn, from a One Welfare perspective. Twenty qualitative interviews were conducted with selected stakeholders involved in emergency responses and their co-ordination. Results from interviews were extracted and are presented as a description of the Danish emergency management procedures in situations where pig transport vehicles overturn in a traffic accident. The description is followed by a discussion of six identified themes related to animal welfare and One Welfare in such situations: (1) Standard operating procedures; (2) Balancing animal welfare and work safety; (3) Roles, education and experience; (4) Communication, time and access to animals; (5) Debriefing; and (6) Killing of animals. Overall, the analyses of the interviews showed that the emergency response at an overturned pig transport vehicle involves different professional groups, requires technical knowledge regarding animal transport vehicles as well as knowledge of the species involved and how to handle the animals. The results are discussed from a One Welfare perspective, suggesting that these emergency responses include an inherent societal prioritisation dilemma involving the balancing of, for example, training, preparation and debriefing of different professional groups. Further research is needed to address ethical considerations, share best practices, and enhance emergency protocols.